A kind of crack-resistant concrete and preparation method thereof

By using a combined additive of emulsifier, highly absorbent resin particles and expansion agent in concrete, the problem of shrinkage and cracking in concrete is solved, which significantly improves crack resistance and extends the service life of the structure.

CN119019127BActive Publication Date: 2025-02-11LANGFANG ZELONG CONCRETE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411514198.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-02-11
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

More than 80% of the cracks in concrete structures are caused by shrinkage and deformation, resulting in structural leakage, accelerated transmission of harmful ions, and even threatened the safety and service life of the structure.

Method used

Emulsifier, highly absorbent resin particles and expansion agents are used as additives to form a stable water-resistance film on the concrete surface to slow down moisture evaporation, compensate for the self-shrinkage and drying shrinkage of concrete, and reduce the probability of cracks.

Benefits of technology

It significantly reduces the plastic shrinkage and cracking of concrete, improves crack resistance, extends the service life of the structure, and reduces the probability of cracking.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a crack-resistant concrete and a preparation method thereof, belonging to the technical field of concrete. The technical scheme thereof mainly comprises a crack-resistant concrete, comprising the following components in parts by weight: 350-420 parts of cementitious materials, 800-900 parts of fine aggregates, 950-1000 parts of coarse aggregates, 7-11 parts of polycarboxylic acid water-reducing agents, 10-20 parts of additives, and 140-170 parts of water; the additives comprise an emulsifier, highly absorbent resin particles, and an expansion agent in a weight ratio of 1: (1.2-1.6): (0.4-0.6), so as to achieve the effect of improving the crack resistance of the concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to a crack-resistant concrete and a preparation method thereof. Background Art

[0002] Shrinkage cracking of concrete is a major technical problem that has long plagued the engineering community. Engineering practice has shown that more than 80% of cracks in concrete structures are caused by different shrinkage deformations. Shrinkage cracks can cause structural leakage and increase the transmission rate of harmful ions. In severe cases, they can threaten the long-term safety of the structure and shorten its service life. With the advancement of major infrastructure projects in my country to harsh environments such as plateaus, deserts, and oceans with large temperature differences, extreme dryness, and strong corrosion, as well as the complexity of concrete composition caused by the scarcity of oil and fat raw materials and the widespread use of industrial waste, shrinkage cracking of concrete and the resulting damage have become more prominent. How to suppress shrinkage cracking of concrete is an urgent problem to be solved in concrete engineering construction.

[0003] At present, the commonly used method to solve the problem of concrete cracking is to introduce fibers into concrete. Currently, commonly used fibers and concrete are thermal expansion and contraction materials, such as synthetic fibers such as polypropylene fibers, polyester fibers, polyvinyl alcohol fibers, and steel fibers. When the temperature of concrete rises and expands, the fibers expand accordingly. When the temperature of concrete decreases and contracts, the fibers also contract. Taking steel fibers as an example, their thermal expansion coefficient is greater than that of concrete. As the temperature rises, the thermal expansion and elongation of steel fibers causes tensile stress on the interface cementitious slurry, resulting in the initiation of microcracks in the interface area. The shrinkage effect in the cooling stage intensifies the growth of cracks, and finally forms macro cracks under the action of multi-field coupling. Therefore, the method of introducing fibers into concrete cannot effectively solve the problem of concrete cracks. Summary of the invention

[0004] In order to improve the anti-cracking performance of concrete, the present invention provides a crack-resistant concrete and a preparation method thereof.

[0005] The first object of the present invention is to provide a crack-resistant concrete, which adopts the following technical scheme:

[0006] A crack-resistant concrete comprises the following components in parts by weight: 350-420 parts of cementitious materials, 800-900 parts of fine aggregates, 950-1000 parts of coarse aggregates, 7-11 parts of polycarboxylic acid water-reducing agents, 10-20 parts of additives, and 140-170 parts of water; the additives comprise an emulsifier, highly water-absorbent resin particles, and an expansion agent in a weight ratio of 1: (1.2-1.6): (0.4-0.6).

[0007] By adopting the above technical solution, the addition of the emulsifier in the present application can form a dense and stable monomolecular film on the surface of the concrete, reduce the evaporation rate of water on the surface of the concrete, thereby achieving the effect of inhibiting water evaporation, and then significantly reducing the plastic shrinkage cracking of the concrete. The use of super absorbent resin particles and expansion agent can well compensate for the autogenous shrinkage and drying shrinkage of concrete, and the growth of the expansion product can fill the holes formed by the super absorbent resin after releasing water. When the super absorbent resin is subjected to the osmotic pressure and self-drying effect during the cement hydration process, the super absorbent resin can release the stored water into the surrounding cement matrix, which can promote the hydration of cement while also promoting the hydration of the expansion agent, increasing the capillary saturation and the relative humidity of the system, reducing the capillary negative pressure, and slowing down the decrease in humidity inside the concrete, thereby reducing or even eliminating autogenous shrinkage.

[0008] Preferably, the emulsifier is one or both of octylphenol polyoxyethylene ether and polyethylene glycol octyl ether.

[0009] Preferably, the weight ratio of the polyoxyethylene octylphenol ether to the polyethylene glycol octyl ether is 1:(0.8-1.2).

[0010] By adopting the above technical scheme, when the emulsifier is selected from one or a combination of octylphenol polyoxyethylene ether and polyethylene glycol octyl ether, a stable water inhibition film can be effectively formed on the concrete surface, slowing down the evaporation of water in the concrete and improving the anti-cracking effect of the concrete.

[0011] Preferably, the super absorbent resin is obtained by the following preparation method: acrylic acid, sodium hydroxide, acrylamide, N'N-methylenebisacrylamide, potassium persulfate and water are prepared into a mixed solution in a weight ratio of 20:8:2.9:0.034:0.18:5, stirred and mixed, and stirred and reacted in a water bath at 70±5°C for 2h, and then taken out, dried and crushed to obtain super absorbent resin particles.

[0012] Preferably, calcium sulfate and nano-silicon dioxide are further added in the preparation of the super absorbent resin, wherein the amount of calcium sulfate added is 2-5% by weight of the acrylic acid, and the amount of nano-silicon dioxide added is 4-8% by weight of the acrylic acid.

[0013] By adopting the above technical scheme, after adding calcium sulfate and nano-silicon dioxide in the preparation of super absorbent resin, calcium sulfate and nano-silicon dioxide can enter the interior of the super absorbent resin, and release calcium ions and sulfate ions to the periphery of the pores during the water release process. In addition, the volcanic ash effect of silicon dioxide promotes the hydration degree of cement, increases the production amount of calcium aluminate and hydrated calcium silicate, and can effectively fill the pores formed after the super absorbent resin releases water to a certain extent, thereby reducing the self-shrinkage performance of concrete and improving the anti-cracking effect of concrete.

[0014] Preferably, the average particle size of the super absorbent resin particles is 100-200 meshes.

[0015] By adopting the above technical solution, when the average particle size of the super absorbent resin particles is between 100-200 meshes, the pore size formed by the water release can be effectively reduced, thereby reducing the adverse effect on the strength of concrete.

[0016] Preferably, the additive further includes citric acid and calcium nitrate, and the weight ratio of the emulsifier: super absorbent resin particles: expander: citric acid: calcium nitrate is 1: (1.2-1.6): (0.4-0.6): (0.2-0.4): (0.7-1.0).

[0017] By adopting the above technical solution, the addition of citric acid and calcium nitrate in the additives can reduce the hydration heat release rate of cement during the accelerated hydration period, effectively reduce the temperature peak of the concrete structure during the hydration period, reduce the amount of water evaporation, and further improve the crack resistance of concrete.

[0018] Preferably, the expansion agent is a magnesium oxide expansion agent.

[0019] The second object of the present invention is to provide a method for preparing the crack-resistant concrete as described above, comprising the following steps:

[0020] S1, stirring and mixing the additive and water accounting for 30% of the total weight of the water to obtain a mixture A;

[0021] S2. Add cementitious material, polycarboxylate water reducer, remaining water, fine aggregate and coarse aggregate into mixture A, stir and mix evenly to obtain crack-resistant concrete.

[0022] In summary, the present invention has the following beneficial effects:

[0023] 1. The combination of emulsifier, super absorbent resin particles and expansion agent in the additive can, on the one hand, inhibit the evaporation of water during cement hydration, and on the other hand, release part of the water in the later stage of cement hydration to compensate for the self-shrinkage and drying shrinkage of concrete, thereby reducing the probability of cracks in concrete due to shrinkage and improving the crack resistance of concrete.

[0024] 2. The addition of calcium sulfate and silicon dioxide in the preparation of super absorbent resin can effectively fill the holes left after the super absorbent resin releases water, reduce the impact of the super absorbent resin on the strength of concrete, and at the same time improve the crack resistance of concrete.

[0025] 3. The addition of citric acid and calcium nitrate in the additives reduces the hydration heat release rate during the accelerated hydration period of cement, effectively reduces the temperature peak of the concrete structure during the hydration period, reduces the amount of water evaporation, and can further improve the crack resistance of concrete. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below with reference to the embodiments.

[0027] The raw materials used in this application are all commercially available. Example 1

[0028] A method for preparing crack-resistant concrete comprises the following steps:

[0029] S1. Stir and mix 10 kg of additives and 30% of the total weight of water (i.e., 42 kg) to obtain a mixture A; wherein the additives include octylphenol polyoxyethylene ether, super absorbent resin particles, and magnesium oxide expansion agent in a weight ratio of 1:1.2:0.4, i.e., the amount of octylphenol polyoxyethylene ether is 3.85 kg, the amount of super absorbent resin is 4.62 kg, and the amount of magnesium oxide expansion agent is 1.53 kg;

[0030] The super absorbent resin is obtained by the following preparation method: acrylic acid, sodium hydroxide, acrylamide, N'N-methylenebisacrylamide, potassium persulfate and water are prepared into a mixed solution in a weight ratio of 20:8:2.9:0.034:0.18:5, stirred and mixed, stirred and reacted in a water bath at 70±5°C for 2h, and then taken out, dried and crushed into super absorbent resin particles with an average particle size of 100 mesh;

[0031] S2. Add 350 kg of cementitious material, 7 kg of polycarboxylate water-reducing agent, 98 kg of remaining water, 800 kg of fine aggregate and 950 kg of coarse aggregate into mixture A and stir and mix them evenly to obtain crack-resistant concrete, wherein the cementitious material consists of cement, fly ash and mineral powder in a weight ratio of 1:0.2:0.3, that is, the amount of cement is 233 kg, the amount of fly ash is 47 kg, and the amount of mineral powder is 70 kg. Example 2

[0032] A method for preparing crack-resistant concrete comprises the following steps:

[0033] S1. Stir and mix 15 kg of additives and 30% of the total weight of water (i.e., 48 kg) to obtain a mixture A; wherein the additives include octylphenol polyoxyethylene ether, super absorbent resin particles, and magnesium oxide expansion agent in a weight ratio of 1:1.2:0.4, i.e., the amount of octylphenol polyoxyethylene ether is 5.77 kg, the amount of super absorbent resin is 6.92 kg, and the amount of magnesium oxide expansion agent is 2.31 kg;

[0034] The super absorbent resin is obtained by the following preparation method: acrylic acid, sodium hydroxide, acrylamide, N'N-methylenebisacrylamide, potassium persulfate and water are prepared into a mixed solution in a weight ratio of 20:8:2.9:0.034:0.18:5, stirred and mixed, stirred and reacted in a water bath at 70±5°C for 2h, and then taken out, dried and crushed into super absorbent resin particles with an average particle size of 100 mesh;

[0035] S2. Add 380 kg of cementitious material, 9 kg of polycarboxylate water-reducing agent, the remaining 112 kg of water, 850 kg of fine aggregate and 980 kg of coarse aggregate to the mixture A and stir and mix evenly to obtain crack-resistant concrete, wherein the cementitious material consists of cement, fly ash and mineral powder in a weight ratio of 1:0.2:0.3, that is, the amount of cement is 253 kg, the amount of fly ash is 51 kg, and the amount of mineral powder is 76 kg. Example 3

[0036] A method for preparing crack-resistant concrete comprises the following steps:

[0037] S1. Stir and mix 20 kg of additives and 30% of the total weight of water (i.e., 51 kg) to obtain a mixture A; wherein the additives include octylphenol polyoxyethylene ether, super absorbent resin particles, and magnesium oxide expansion agent in a weight ratio of 1:1.2:0.4, i.e., the amount of octylphenol polyoxyethylene ether is 7.69 kg, the amount of super absorbent resin is 9.23 kg, and the amount of magnesium oxide expansion agent is 3.08 kg;

[0038] The super absorbent resin is obtained by the following preparation method: acrylic acid, sodium hydroxide, acrylamide, N'N-methylenebisacrylamide, potassium persulfate and water are prepared into a mixed solution in a weight ratio of 20:8:2.9:0.034:0.18:5, stirred and mixed, stirred and reacted in a water bath at 70±5°C for 2h, and then taken out, dried and crushed into super absorbent resin particles with an average particle size of 100 mesh;

[0039] S2. Add 420 kg of cementitious material, 11 kg of polycarboxylate water-reducing agent, the remaining 119 kg of water, 900 kg of fine aggregate and 1000 kg of coarse aggregate to the mixture A and stir and mix evenly to obtain crack-resistant concrete, wherein the cementitious material consists of cement, fly ash and mineral powder in a weight ratio of 1:0.2:0.3, that is, the amount of cement is 280 kg, the amount of fly ash is 56 kg, and the amount of mineral powder is 84 kg. Example 4

[0040] A method for preparing crack-resistant concrete, which is different from Example 2 in that an equal amount of polyethylene glycol octyl ether is used to replace 4-octylphenol polyoxyethylene ether, and the rest is the same as Example 2. Example 5

[0041] A method for preparing crack-resistant concrete, which is different from Example 2 in that the weight ratio of octylphenol polyoxyethylene ether, super absorbent resin particles and magnesium oxide expansion agent is 1:1.4:0.5, and the rest is the same as Example 2. Example 6

[0042] A method for preparing crack-resistant concrete, which is different from Example 2 in that the weight ratio of octylphenol polyoxyethylene ether, super absorbent resin particles and magnesium oxide expansion agent is 1:1.6:0.6, and the rest is the same as Example 2. Example 7

[0043] A method for preparing crack-resistant concrete, which is different from Example 2 in that, when the total amount of emulsifier is 5.77 kg, the emulsifier is a mixture of octylphenol polyoxyethylene ether and polyethylene glycol octyl ether in a weight ratio of 1:0.8, i.e., 3.21 kg of octylphenol polyoxyethylene ether and 2.56 kg of polyethylene glycol octyl ether, and the rest is the same as Example 2. Example 8

[0044] A method for preparing crack-resistant concrete, which is different from Example 2 in that, when the total amount of emulsifier is 5.77 kg, the emulsifier is a mixture of 4-octylphenol polyoxyethylene ether and polyethylene glycol octyl ether in a weight ratio of 1:1, that is, 2.885 kg of 4-octylphenol polyoxyethylene ether and 2.885 kg of polyethylene glycol octyl ether, and the rest is the same as Example 2. Example 9

[0045] A method for preparing crack-resistant concrete, which is different from Example 2 in that, when the total amount of emulsifier is 5.77 kg, the emulsifier is a mixture of octylphenol polyoxyethylene ether and polyethylene glycol octyl ether in a weight ratio of 1:1.2, that is, 2.62 kg of octylphenol polyoxyethylene ether and 3.15 kg of polyethylene glycol octyl ether, and the rest is the same as Example 2. Example 10

[0046] A method for preparing crack-resistant concrete, which is different from Example 2 in that the raw materials in the preparation of super absorbent resin are different, specifically: acrylic acid, sodium hydroxide, acrylamide, N'N-methylenebisacrylamide, potassium persulfate and water are prepared into a mixed solution in a weight ratio of 20:8:2.9:0.034:0.18:5, and calcium sulfate with a weight of 2% of acrylic acid and nano-silicon dioxide with a weight of 4% of acrylic acid are added to the mixed solution, after stirring and mixing, stirring and reacting for 2 hours in a water bath at 70±5°C, taking out, drying and crushing into super absorbent resin particles with an average particle size of 100 mesh. Embodiment 11

[0047] A method for preparing crack-resistant concrete, which is different from Example 2 in that the raw materials in the preparation of super absorbent resin are different, specifically: acrylic acid, sodium hydroxide, acrylamide, N'N-methylenebisacrylamide, potassium persulfate and water are prepared into a mixed solution in a weight ratio of 20:8:2.9:0.034:0.18:5, and calcium sulfate with a weight of 5% of acrylic acid and nano-silicon dioxide with a weight of 8% of acrylic acid are added to the mixed solution, after stirring and mixing, stirring and reacting for 2 hours in a water bath at 70±5°C, taking out, drying and crushing into super absorbent resin particles with an average particle size of 100 mesh. Example 12

[0048] A method for preparing crack-resistant concrete, which is different from Example 2 in that the raw materials in the preparation of super absorbent resin are different, specifically: acrylic acid, sodium hydroxide, acrylamide, N'N-methylenebisacrylamide, potassium persulfate and water are prepared into a mixed solution in a weight ratio of 20:8:2.9:0.034:0.18:5, and calcium sulfate with a weight ratio of 5% of acrylic acid is added to the mixed solution, after stirring and mixing, stirring and reacting for 2 hours in a water bath at 70±5°C, taking out, drying and crushing into super absorbent resin particles with an average particle size of 100 mesh. Embodiment 13

[0049] A method for preparing crack-resistant concrete, which is different from Example 2 in that the raw materials in the preparation of super absorbent resin are different, specifically: acrylic acid, sodium hydroxide, acrylamide, N'N-methylenebisacrylamide, potassium persulfate and water are prepared into a mixed solution in a weight ratio of 20:8:2.9:0.034:0.18:5, and nano-silicon dioxide with an acrylic acid weight of 8% is added to the mixed solution, after stirring and mixing, stirring and reacting for 2 hours in a water bath at 70±5°C, taking out, drying and crushing into super absorbent resin particles with an average particle size of 100 mesh. Embodiment 14

[0050] A method for preparing crack-resistant concrete, which is different from Example 2 in that the total amount of additives is 15 kg, and the additives also include citric acid and calcium nitrate, wherein the weight ratio of emulsifier: super absorbent resin particles: magnesium oxide expansion agent: citric acid: calcium nitrate is 1:1.2:0.4:0.2:0.7, wherein the emulsifier is composed of octylphenol polyoxyethylene ether and polyethylene glycol octyl ether in a weight ratio of 1:1, and the rest are the same as Example 2. Embodiment 15

[0051] A method for preparing crack-resistant concrete, which is different from Example 2 in that the total amount of additives is 15 kg, and the additives also include citric acid and calcium nitrate, wherein the weight ratio of emulsifier: super absorbent resin particles: magnesium oxide expansion agent: citric acid: calcium nitrate is 1:1.2:0.4:0.4:1, wherein the emulsifier is composed of octylphenol polyoxyethylene ether and polyethylene glycol octyl ether in a weight ratio of 1:1, and the rest are the same as Example 2. Example 16

[0052] A method for preparing crack-resistant concrete, which is different from Example 14 in that the total amount of additives is 15 kg, and the additives also include citric acid and calcium nitrate, wherein the weight ratio of emulsifier: super absorbent resin particles: magnesium oxide expansion agent: citric acid: calcium nitrate is 1:1.2:0.4:0.2:0.7, and the emulsifier is composed of octylphenol polyoxyethylene ether and polyethylene glycol octyl ether in a weight ratio of 1:1;

[0053] The raw materials in the preparation of the super absorbent resin are different. Specifically, acrylic acid, sodium hydroxide, acrylamide, N'N-methylenebisacrylamide, potassium persulfate and water are prepared into a mixed solution in a weight ratio of 20:8:2.9:0.034:0.18:5, and calcium sulfate with a weight of 2% of acrylic acid and nano-silicon dioxide with a weight of 4% of acrylic acid are added to the mixed solution. After stirring and mixing, the mixture is stirred and reacted in a water bath at 70±5°C for 2h, and then taken out, dried and crushed into super absorbent resin particles with an average particle size of 100 mesh. The rest is the same as Example 14. Embodiment 17

[0054] A method for preparing crack-resistant concrete, which is different from Example 2 in that the average particle size of the super absorbent resin particles is 200 meshes, and the rest is the same as Example 2. Embodiment 18

[0055] A method for preparing crack-resistant concrete, which is different from Example 2 in that the average particle size of the super absorbent resin particles is 300 meshes, and the rest is the same as Example 2. Embodiment 19

[0056] A method for preparing crack-resistant concrete, which is different from Example 2 in that the average particle size of the super absorbent resin particles is 50 meshes, and the rest is the same as Example 2. Comparative Example 1

[0057] A method for preparing crack-resistant concrete, which is different from Example 2 in that there is no additive in the raw material components, and the rest is the same as Example 2. Comparative Example 2

[0058] A method for preparing crack-resistant concrete, which is different from Example 2 in that no octylphenol polyoxyethylene ether is included in the additive, the weight ratio of super absorbent resin particles to magnesium oxide expansion agent is 1.2:0.4, and the rest is the same as Example 2. Comparative Example 3

[0059] A method for preparing crack-resistant concrete, which is different from Example 2 in that there are no super absorbent resin particles in the additive, the weight ratio of octylphenol polyoxyethylene ether to magnesium oxide expansion agent is 1:0.4, and the rest is the same as Example 2. Comparative Example 4

[0060] A method for preparing crack-resistant concrete, which is different from Example 2 in that no magnesium oxide expansion agent is included in the additive, the weight ratio of octylphenol polyoxyethylene ether to super absorbent resin is 1:1.2, and the rest is the same as Example 2.

[0061] Control group

[0062] A method for preparing crack-resistant concrete, which is different from Example 2 in that an equal amount of steel fibers is used to replace the additives, and the rest is the same as Example 2.

[0063] Performance Testing

[0064] The concrete obtained from the above examples and comparative examples was tested for 28-day compressive strength, 28-day splitting tensile strength and 28-day crack resistance. The test results are shown in Table 1.

[0065] Table 1 Concrete performance test results

[0066]

[0067] From the table above we can see that:

[0068] The crack resistance of the crack-resistant concrete obtained in the embodiment of the present application is much improved compared with that of the control group, indicating that adding an additive consisting of an emulsifier, super absorbent resin particles and a magnesium oxide expansion agent to the concrete can effectively improve the crack resistance of the concrete while also ensuring the strength of the concrete.

[0069] Compared with Example 2, when the total amount of additives remains unchanged, as the proportions of octylphenol polyoxyethylene ether, super absorbent resin particles and magnesium oxide expansion agent change, the crack resistance of the concrete obtained in Examples 5-6 is improved compared with that in Example 2.

[0070] Compared with Example 2, when the total amount of the emulsifier remains unchanged and the emulsifier is composed of 4-octylphenol polyoxyethylene ether and polyethylene glycol octyl ether, the crack resistance of the concrete obtained in Examples 7-9 is significantly improved compared with that in Example 2. It can be seen that the combined use of the two emulsifiers can effectively slow down the evaporation of water during the hydration reaction, thereby further improving the crack resistance of the concrete.

[0071] Compared with Example 2, when calcium sulfate and nano-silica are added to the super absorbent resin during preparation, the crack resistance and splitting tensile strength of the concrete obtained in Examples 10-11 are significantly improved compared with those in Example 2. It can be seen that the combined use of calcium persulfate and nano-silica can effectively fill the holes left after the super absorbent resin releases water, thereby effectively improving the crack resistance of the concrete.

[0072] Compared with Example 2, when calcium sulfate or nano silicon dioxide is added in the preparation of the super absorbent resin, the crack resistance of the concrete obtained in Examples 12-13 is improved compared with Example 2, but is reduced compared with Example 11, which can further illustrate that the combination of calcium sulfate and silicon dioxide can effectively improve the crack resistance of concrete.

[0073] Compared with Example 2, when citric acid and calcium nitrate are added to the additives, the crack resistance of the concrete obtained in Examples 14-15 is significantly improved compared with that in Example 2. It can be seen that the addition of citric acid and calcium nitrate can effectively reduce the temperature during the hydration process of concrete, thereby reducing the evaporation of water in the concrete and reducing the shrinkage performance of the concrete.

[0074] Compared with Example 14, when calcium sulfate and nano-silica are added to the super absorbent resin on the basis of citric acid and calcium nitrate, and the emulsifier is a mixture of octylphenol polyoxyethylene ether and polyethylene glycol octyl ether, the compressive strength and splitting tensile strength of the concrete obtained in Example 16 are increased, and no cracks appear in the concrete after 28 days. It can be seen that the scheme of Example 16 effectively improves the crack resistance of the concrete.

[0075] Compared with Example 2, when the average particle size of the super absorbent resin particles is 300 mesh or 50 mesh, the crack resistance of the concrete obtained in Examples 18-19 is significantly reduced compared with that in Example 2. The reason is that when the mesh number is too large, the super absorbent resin particles are too small and absorb less water, and the subsequent hydration supplement effect is not obvious. When the mesh number is too small, the particle size of the super absorbent resin particles is too large, and the water absorption is large. The holes left after water release are large, which also reduces the strength and crack resistance of the concrete.

[0076] Compared with Example 2, when the components lack additives or lack a certain component of the additives, the crack resistance of the concrete obtained in Comparative Examples 1-4 is greatly reduced compared with Example 2. It can be seen that the addition of additives can effectively improve the crack resistance of concrete.

[0077] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A crack-resistant concrete, characterized in that: The invention comprises the following components in parts by weight: 350-420 parts of cementitious material, 800-900 parts of fine aggregate, 950-1000 parts of coarse aggregate, 7-11 parts of polycarboxylic acid water reducer, 10-20 parts of additives and 140-170 parts of water; the additives comprise an emulsifier, highly absorbent resin particles, an expander, citric acid and calcium nitrate in a weight ratio of 1: (1.2-1.6): (0.4-0.6): (0.2-0.4): (0.7-1.0); the emulsifier is composed of octylphenol polyoxyethylene ether and polyethylene glycol octyl ether in a weight ratio of 1: (0.8-1.2); The super absorbent resin is obtained by the following preparation method: acrylic acid, sodium hydroxide, acrylamide, N'N-methylenebisacrylamide, potassium persulfate and water are prepared into a mixed solution in a weight ratio of 20:8:2.9:0.034:0.18:5, stirred and mixed, stirred and reacted for 2 hours in a water bath at 70±5°C, and then taken out, dried and crushed to obtain super absorbent resin particles; calcium sulfate and nano-silicon dioxide are also added in the preparation of the super absorbent resin, the amount of calcium sulfate added is 2-5% of the weight of acrylic acid, and the amount of nano-silicon dioxide added is 4-8% of the weight of acrylic acid.

2. The crack-resistant concrete according to claim 1, characterized in that: The average particle size of the super absorbent resin particles is 100-200 meshes.

3. The crack-resistant concrete according to claim 1, characterized in that: The expansion agent is a magnesium oxide expansion agent.

4. A method for preparing crack-resistant concrete according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: S1, stirring and mixing the additive and water accounting for 30% of the total weight of the water to obtain a mixture A; S2. Add cementitious material, polycarboxylate water reducer, remaining water, fine aggregate and coarse aggregate into mixture A, stir and mix evenly to obtain crack-resistant concrete.

Citation Information

Patent Citations

  • High-crack-resistance concrete for plateau environment and preparation method

    CN112694299A